Organic nitrogen uptake by plants: reevaluation by position-specific labeling of amino acids (Biogeochemistry, 2015)
Current studies suggest that many plants are able to take up not only inorganic nitrogen (N) but also organic N. We used the novel tool of position-specific isotope labeling to improve the quantification of intact amino acid uptake and to deepen our understanding of the processes occurring at the root-soil-microorganism interface. Position-specific 14C and 15N labeled alanine enabled us to trace the uptake of C from individual molecule positions by Zea mays, Lupinus albus and Cichorium intybus. Uniformly 14C labeled alanine and acetate and inorganic 15NH4+ and 15NO3− were applied as controls. Equal uptake of uniformly 14C labeled alanine and acetate showed that plant uptake of low molecular weight organic substances (LMWOS) is independent of N in the molecule. 14C uptake from individual molecule positions of alanine strongly differed: this confirmed that soil microorganisms cleaved alanine within 6 h into transformation products, which were then taken up by the plants. Microbial utilization strongly outcompeted the plant uptake of LMWOS in agricultural soils. This study revealed that position-specific labeling is an innovative tool that enables separation of the intact uptake from the uptake of molecule fragments and improves the understanding of competing processes for LMWOS utilization in the rhizosphere.